Biological effect of biodegradable mulch films on maize and their degradation properties - Hu Hongliang; Han Zhigang; Zhang Guoping (浙江大学学报. 农业与生命科学版)
Over the past few decades, the use of traditional mulch film made of poly-ethylene enhanced agriculture production worldwide, and meanwhile raised a range of agricultural and ecological concern associated with degradation of soil fertility due to residue accumulation. It has become an increasingly challenging issue for agricultural sustainability. As a consequence, biodegradable films are proposed as an effective solution to alleviate this issue. Among them, poly (butyleneadipate-co-terephthalate) (PBAT) , a biodegradable aliphatic-aromatic polyester, possesses similar mechanical properties to polyethylene and therefore is generally considered an ideal substitute for conventional films. This study aimed at making a comprehensive evaluation of several recently developed biodegradable films by comparing their biological effects and field degradation properties.Five biodegradable films with a main component of PBAT were applied to cover the beds of maize in an experimental field, and then the soil temperature, plant growth indices and yield components of maize were investigated. Meanwhile, the field degradation of both biodegradable and conventional films was assessed by a standard of degradation degree.The results showed that the biodegradable films, compared to bare plot, markedly raised soil temperatures at three observation depths (5 cm, 10 cm and 15 cm) and this heat capturing effect was as pronounced as the conventional polyethylene film. The temperature boosting effect varied with soil depth and time, i. e., the biggest diurnal fluctuation of temperature occurred at the depth of 5 cm in each treatment, while the least was at the depth of 15 cm. The growth of maize was significantly stimulated in all mulched plots, with the occurrence of seedling emergence and silking stage being 3-5 days and 10-13 days earlier than bare plots, respectively. A minor advantage of biodegradable film over conventional film was also observed. The highest chlorophyll content (indicated by SPAD) was found in the bare plot, followed by M2, and M1 was the lowest, yet there were no significant differences among mulching treatments. By contrast, leaf area indices (LAI) of the biodegradable films were significantly higher than non-mulched plot, with the highest in M2. At the jointing stage, the plant height under all mulched plots were greater than that under the bare plot. While at the maturity stage, plants in the bare plot had the highest height, and there were no significant differences among the five biodegradable films. The largest accumulation of nitrogen, phosphate and potassium in plants occurred in the bare plot, being significantly higher than in the mulched plots. The fresh yield, kernels per ear and 100-kernel mass were significantly larger in all mulched plots than in the bare plot. The yield per plot of the biodegradable films was higher than that of the conventional film, yet no difference existed between the biodegradable films and the conventional film in terms of kernels per ear and 100-kernel mass. Field observation revealed that the biodegradable films started losing integrity at approximately 20 days after application in the field. The earliest clear disappearance of film started at 90 days after application for M2. While the relatively slow degradation was found in M1 and M5, which were torn into separate subunits with roughly 10 cm cracks after 100 days of field exposure, reaching the 4th period of degradation.In sum, all the biodegradable films are capable of enhancing maize growth by improving soil temperature and even contribute a larger economic yield than the conventional film; moreover, the biodegradable films maintain stability for approximately 20 days after application in the field and disappear after 90-100 days, demonstrating the applicable effectiveness for mulching as a substitute of the conventional film.